Large eddy simulation of airfoil self-noise using OpenFOAM. Issue 1 (2nd January 2018) - Kamliya Jawahar, Hasan; Lin, Yujing; Savill, Mark
Abstract : Purpose: The purpose of this paper is to investigate airfoil self-noise generation and propagation by using a hybrid method based on the large-eddy simulation (LES) approach and Curle's acoustic analogy as implemented in OpenFOAM. Design/methodology/approach: Large-eddy simulation of near-field flow over a NACA6512-63 airfoil at zero angle of attack with a boundary layer trip at Rec = 1.9 × 10 5 has been carried out using the OpenFOAM® computational fluid dynamics (CFD) code. Calculated flow results are compared with published experimental data. The LES includes the wind tunnel installation effects by using appropriate inflow boundary conditions obtained from a RANS κ – ω SST model computation of the whole wind tunnel domain. Far-field noise prediction was achieved by an integral method based on Curle's acoustic analogy. The predicted sound pressure levels are validated against the experimental data at various frequency ranges. Findings: The numerical results presented in this paper show that the flow features around a NACA6512-63 airfoil have been correctly captured in OpenFOAM LES calculations. The mean surface pressure distributions and the local pressure peaks for the step trip setup agree very well with the experimental measurements. Aeroacoustic prediction using Curle's analogy shows an overall agreement with the experimental data. The sound pressure level-frequency spectral analysis produces very similar data at low to medium frequency, whereas the experimentally observed levels are slightly over predicted at a higher frequency range. Practical implications: This study has achieved and evaluated an alternative aeroacoustic simulation method based on the combination of LES with a simple Smagorinsky SGS model and Curle's analogy, as implemented in the OpenFOAM CFD code. The unsteady velocity/pressure source data produced can be used for any simpler analytically based far-field noise prediction scheme. Originality/value: A complete integration of the LES and Curle's acoustic analogy for aeroacoustic simulations has been achieved in OpenFOAM. The capability and accuracy of the hybrid method are fully evaluated for high-camber airfoil self-noise predictions. Wind tunnel installation effects have been incorporated properly into the LES.